Enhancing English Teachers’ Capacity to Implement Differentiated Instruction in Post-Disaster School Settings: Reflections and Pedagogical Recommendations from a Community Service Action in Pidie Jaya, Aceh - Khasinah, Siti (Bansigom Na Publisher, 2026)
Post-disaster school conditions present complex challenges for English teachers, including damaged infrastructure, limited learning resources, and diverse student learning needs. In response to these challenges, a community service program in the form of a seminar was conducted for disaster-affected communities, including teachers in general and English teachers in particular, in Pidie Jaya, Aceh. This article aims to provide pedagogical reflections and recommendations on how English teachers can implement differentiated instruction in post-disaster school settings. Drawing on theories of differentiated instruction, post-disaster education, and English language teaching, this article outlines practical strategies for adapting teaching methods, materials, and media to students’ readiness, interests, and learning profiles. Rather than reporting empirical outcomes, this paper emphasizes conceptual guidance and professional recommendations derived from the seminar content and discussions. The article contributes to community capacity building by offering a flexible instructional framework that supports teaching continuity and educational resilience in post-disaster contexts.